Gender Representation through Equal Rights Amendment of 1972 in the Judiciary : Case Study: On the Basis of Sex (2018) - Chelaouchi, Imane; Bentria, Khedidja; Guellil, Assia (University of Ammar Theledji -Laghouat, 2022)
The quest for identity for both woman and man is one of the pivotal themes, which led to an upheaval in the American community. This constant quest has become more complex in recent years, as people started asking for their identities and who are they, as individuals within a society. For that reason, woman of achievement like: Ruth Bader Ginsburg was looking for self-identity by facing dehumanization that motivated her personality. Moreover, she found herself revolting against different segregations, adopting feminist ideologies and gender principles looking for equal treatment. This study is an attempt to examine women’s and men’s place fighting discrimination in the law sphere. The main objective of the study is to explore how women were discriminated, demanding for their rights as a resolution rather than a conflict. This research follows an exploratory-expository method to illustrate women’s suffering through years until the bill of the Equal Rights Amendment was passed and has reduced discrimination through law. The core value of the movie is how power and beauty were demonstrated in Ginsburg’s legal battle the gender discrimination case which was represented in the plaintiff in an appeal of the 1972 tax discrimination case Moritz V. Commissioner of internal revenue. Ginsburg argued the unconstitutionally of the code after the presentation of the tax. After all, Ginsburg succeed to change the tax law under the Equal Rights Amendment.